Juvenile Ossifying Fibroma of the Maxilla: A Case Report (Anwer Khan Modern Medical College Journal, 2013)
Juvenile ossifying fibroma (JOF) is a rare fibro-osseous neoplasm that arises within the craniofacial bones in individuals under 15 years of age. It affects both males and females equally. It has the potential for excessive growth, bone destruction, and recurrence. It is more aggressive than ossifying fibroma. Recurrence rate ranges from 30% to 58% .We report a case of 11-year-old male child presented with a painless, progressive swelling of the right face for 8 months. CT scan demonstrated a well-defined, mixed-density mass filling the right maxillary sinus. Under general anaesthesia, surgical excision of the tumour was performed. Histopathologically, excised specimen was identical with fibro-osseous lesion. Juvenile ossifying fibroma (JOF) is aggressive in nature and recurrence rate is high, so early detection and complete surgical excision is essential. DOI: http://dx.doi.org/10.3329/akmmcj.v4i1.13685 AKMMC J 2013: 4(1): 42-44